Risk Factors and Prevalence of Suicide Attempt in Patients with Type 2 Diabetes in the Mexican Population - Gómez-Peralta, Tania Guadalupe (Int J Environ Res Public Health, 2018)
Background: It has been proposed that the risk of death by suicide is higher in patients with diabetes than in the general population. Therefore, it is necessary to investigate the risk factors of suicidal behavior in patients with type 2 diabetes. The aim of the present study was to analyze the prevalence of suicide attempt and determine the risk factors of suicide attempt, in patients with type 2 diabetes in a Mexican population. Methods: Clinic characteristics, anthropometric measurements, biochemical levels, depression, and suicidal behavior were evaluated in 185 Mexican patients with type 2 diabetes. A multivariate logistic regression analysis was performed to find predictive factors of suicide attempt. Results: 11.4% of patients reported previous suicide attempts n = 21). Younger patients (OR: 3.63, 95% CI: 1.29–10.19), having depression (OR: 3.33, 95% CI: 1.13–9.76) and normal BMI (OR: 3.14, 95% CI: 1.11–8.83), were predictive factors of suicide attempt. No other variables in the study showed statistical significance. Conclusions: Our results showed a high prevalence of suicidal behavior in patients with type 2 diabetes. We found that younger age, depression and normal BMI could be risk factors of suicide attempt in these patients. Therefore, psychiatric interventions to prevent depression and suicidal behavior in this population are necessary. New studies using larger samples are necessary to replicate and confirm these results.